POTENTIOMETRIC SENSOR BASED ON SILVER SULFIDE NANOPARTICLES SUPPORTED IN CARBONACEOUS MATERIAL FOR THE DETECTION OF FREE CYANIDE - Alfredo Cardenas-Riojas, Andy; Wong, Ademar [UNESP]; Sotomayor, Maria Del Pilar T. [UNESP]; La Rosa-Toro, Adolfo; Maria Baena-Moncada, Angelica (Soc Brasileira Quimica, 2019)
Two sensors were synthesized for the detection of free cyanide (CN-), based on silver sulfide nanoparticles (Np-Ag2S) supported on Multiwall Carbon Nanotubes (MWCNT) and hierarchical porous carbon (HPC). The Ag2S/HPC400 and Ag2S/MWCNT were characterized by physicochemical techniques such as Raman spectroscopy, X-Ray diffraction (XRD) and Scanning electron microscopy (SEM). These sensors were evaluated against the detection of free cyanide by potentiometry; the stability, reproducibility and linearity of each sensor were determined. A limit of detection of 3.34 mu g L-1 and a limit of quantification of 11.05 mu g L-1 for Ag2S/HPC 400 sensor was obtained; while for the Ag2S/MWCNT sensor a limit of detection and limit of quantification value of 23.17 mu g L-1 and 76.46 mu g L-1 were obtained, respectively. The results show that the presence of carbonaceous materials with a hierarchical structure improves the limits of quantification and detection of the Ag2S/HPC 400 sensor.
Keywords: hierarchical porous carbon; sensors; free cyanide; silver sulfide; multiwall carbon nanotubes